Case Study : Sime Darby Berhad (SDB) - Adam, Yousif (2003)
Sime Darby is truly a well diversified in terms of business activity and market presence. Having exposure in attractive China and Australia, with projected growth of 7.7% and 3.9% in 2003 respectively further arrested earnings volatility.